Gut microbiota-derived butyrate enhances exercise-induced bone mineral density in humans - Xiangya Dou; Pengyu Fu; Yuting Zhang; Yiwen Zhang; Kaiting Ning; Baoqiang Yang; Xuezhou Yang; Yinbo Niu; Dong-En Wang; Huiyun Xu (Mechanobiology in Medicine)
Bone Mineral Density (BMD) is one of the primary markers of bone health. Exercise provides constant mechanical stress to bone, which in turn increases BMD. Gut-bone axis is considered to play an important role in the regulation of exercise on bone. Also, the metabolites of gut microbiota (GM), especially short-chain fatty acids (SCFAs), are thought to be involved in the progress. In this study, by analyzing serum and GM from humans with low and high BMD, we found that exercise indeed enhanced BMD, and butyrate secreted from GM was involved in the regulation.